The regulation and supervision of banks around the world : a new database - Barth, James R., 1943-2023 1943-2023 (Policy research working paper, 2001)
This new and comprehensive database on the regulation and supervision of banks in 107 countries should better inform advice about bank ewgulation and supervision and lower the marginal cost of empirical research